Perception of the cost benefit ratio of the stone crushing activity by actors in the informal sector of the Collines Department in Benin - TOSSOU, FÉLICIEN; Yabi, Ibouraïma; LANDEOU, Rodrigue Codjo; BOKO, MICHEL (My University, 2021)
Artisanal stone crushing is one of the income-generating activities practiced by many populations of the Collines Department in the Republic of Benin. It is a dangerous activity in which the actors ignore the occupational risks. This research was initiated to study the working conditions of crushing operators in the Collines Department, in order to assess the associated occupational risks. The methodological approach adopted to achieve these objectives consists of documentary research, surveys and field interviews with questionnaires, interview guides and direct field observation based on an observation grid. The data were collected from 64 artisanal stone crushers aged over 15 years 12 men and 52 women, ie a sex ratio of 4.3 in favor of women. The study was carried out at 5 sites in three Communes of the Collines Department. The data were processed with SPSS 21 software. The results obtained showed that the median age of the actors is 44 years with a minimum of 18 years and a maximum of 71 years. One in two people have not set foot in school. The average seniority in crushing is 16 years. The work provides less than 10,000f per month for three people out of 5. The daily working time varies from 5 to 12 hours. The majority work 6 days a week (84.4%). The complaints made by those involved in crushing are: heartache (59.4%), low back pain and back pain (12.3%), followed by accidents (9.4%) and respiratory ailments (9.4%). For 4/5, certain times of the year would be more at risk and for 45.3%, it is the rainy season. More than 77% of people recognize that there are specific risks to children, including the risk of accidents. For prevention, the majority of women wear pants to protect their private parts. Wearing shoes is not systematic. No one wears protective equipment for their hands, eyesight, hearing, or airways.
Keywords: Perception; Stone crushing activity; Informal sector; Collines Department in Benin